Pine (Pinus massoniana Lamb.) Needle Extract Supplementation Improves Performance, Egg Quality, Serum Parameters, and the Gut Microbiome in Laying Hens - Guo, Yanxin; Huang, Shimeng; Zhao, Lihong; Zhang, Jianyun; Ji, Cheng; Ma, Qiugang (Frontiers in Nutrition, 2022)
The effects of masson pine (Pinus massoniana Lamb.) needle extract on gastrointestinal disorders and oxidative stress have been widely investigated using experimental models; however, the functions and mechanisms of these effects in chicken models remain unknown. We investigated the effects of masson pine (Pinus massoniana Lamb.) needle extract (PNE) supplementation on performance, egg quality, serum parameters, and the gut microbiome in laying hens. Sixty healthy 50-week-old Peking Pink laying hens with similar body conditions and egg production were randomly divided into the CON (0 mg/kg PNE), PNE100 (100 mg/kg PNE), PNE200 (200 mg/kg PNE), and PNE400 (400 mg/kg PNE) groups, with fifteen replicates per treatment and one hen per replicate. Compared with the CON group, egg mass, feed conversion ratios, and yolk weight were significantly increased (P < 0.01) in the PNE100 group. Dietary supplementation of 100 mg/kg PNE increased the serum total protein, albumin and glucose concentrations (all P < 0.01) and decreased the alanine aminotransferase activity (P < 0.05) compared with those of the controls. Hens in the PNE100 group had reduced serum malondialdehyde levels (P < 0.05) and increased catalase, superoxide dismutase and glutathione peroxidase activities (P < 0.01) compared with those of the CON group. Serum proinflammatory cytokine concentrations of interleukin (IL)-1β, IL-6, and tumor necrosis factor-α were lower (P < 0.01), and the IL-10 level was higher (P < 0.01) in the PNE100 group than in the CON group. Serum IgA, IgG and IgM concentrations were increased in the PNE100 group (P < 0.01). The relative abundance of Bacteroidetes was increased, while the relative abundances of Firmicutes and Proteobacteria were decreased in the PNE100 group. The relative abundances of Vibrio, Shewanella and Lactobacillus were decreased, while the relative abundances of unclassified_o_Bacteroidales, Rikenellaceae_RC9_gut_group, unclassified_f_Rikenellaceae and Butyricicoccaceae were increased in the PNE100 group compared with those of the CON group. PNE supplementation at 100 mg/kg improved the diversity and structure of the gut microbial composition, production performance, egg quality, and serum parameters of laying hens. The laying hens in this study had good production performance when supplemented with 100 mg/kg PNE.